ХҮН АМЫН ШИЛЖИН СУУРЬШИХ ҮЙЛ ЯВЦ: ХОТЖИЛТ БА ХӨГЖЛИЙН СОРИЛТУУД - М.Батбаатар, (Politology, 2023)
The article was written with evidence and fact to identify human settlement some faced problems during urbanization process in Mongolia. Furthemore, author analyzed urban planning experiences of the developed countries and territorialization ofMongolian cities and its perspectives.